The Return of Large Dams to the Development Agenda: A Post-Development Critique - Pearse-Smith, Scott W.D. (Consilience, 2014)
Large dams are making a comeback. Large dams reflect an outdated development paradigm narrowly focused on economic growth through modernization. This article employs a post-development lens to highlight three biases of the narrow development perspective that underlies large dams. First, it views rivers, and nature more generally, as an unrealized source of economic growth and an input to production. Second, it is blind to distributional impacts and is resultantly inequitable: the benefits of large dams are concentrated in the hands of the wealthy, while conditions for the poor do not improve and often worsen. Third, it disempowers those supposedly being developed by de-politicizing the development decisions to pursue large dam projects. Each of these biases is illustrated by reference to the Mekong River Basin’s experience with large dam development. It is concerning, therefore, that large dams seem to be making a resurgence in Asia, Africa and South America, and are once again receiving World Bank support. This article serves as a reminder of why large dams do not deliver equitable development and faded from the development agenda at the turn of the century.